EXPLORING DEMOGRAPHICS AND OUTCOMES FOR SPINAL TUMOURS FOLLOWING SURGERY IN COMBINED MILITARY HOSPITAL, PESHAWAR - Junaid, Muhammad; Asheen, Afeera; Rehman, Muneeb Ur; Rashid, Mamoon Ur; Bukhari, Syed Sarmad; Ahmed, Mamoon (Journal of Ayub Medical College Abbottabad, 2015)
Background: Tumours of the spinal cord, spinal meninges and cauda equina are relatively rare and their spectrum has not been studied extensively in Khyber Pakhtun Khawa province. We describe here the cases of spinal tumours treated in our setup over a period of two years. Methods: This Descriptive Case Series was carried out with of 80 patients operated in our centre from January 2013 to January 2015. The clinical presentation of these tumours as well as demographic findings was analysed. Patients who underwent surgery for their tumours were included in the study. Patients were selected for surgery depending on their radiological and clinical findings. Lesions that were suggestive of metastasis were biopsied and further care was shared between specialized departments depending on the primary source. Results: Male to female ratio was 1.5:1. Most of the spinal tumours were secondary tumours while meningiomas were the most common primary tumours. Most commonly patients belonged to young age group A (below 30 years.) 32.5%. Most common presentation was with paraparesis (27.5%) and paralysis (25%). A majority of patients regained good neurological function and did not show signs of recurrence at 1 year follow up. Conclusion: Given the limited experience at our centre, we believe that a wide range of spinal tumours can be successfully treated provided that clinical end points are kept in mind and treatment is individualized. Frankel grading is useful to assess surgical outcome in the patients.